Implication of Three Dimensional Framework Architecture of Graphitic Carbon Nanosheets for Improving Electrical Conductivity Under Mechanical Deformation - Lim, Yeon-Jeong; Shin, Keun-Young; Lee, Sang-Soo (POLYMER SOC KOREA, 2020)
In this study, based on three-dimensional (3D) framework architecture built-up with two-dimensional (2D) graphitic carbon such as graphene, we have prepared a mechanically robust polymer composite without exhibiting notable deterioration of electrical conductivity under mechanical deformation. In constructing 3D framework comprising of graphitic carbons, two sophisticated methodologies, direct formation of graphitic layers on metal foam by chemical vapor deposition (CVD), and lay-up of reduced graphene oxide (rGO) nanosheets on metal foam have been performed, respectively, and their sustainability of conductive performance under mechanical deformation has been comparatively examined in terms of electrical conductivity change by cyclic mechanical stress. The CVD-synthesized graphene (CGr) framework-embedded PDMS composite, which means a PDMS composite containing 3D graphene framework grown by CVD process, exhibited electrical conductivity of similar to 5 S/m at graphene content of 1.0 wt%, which was similar to 5 orders of magnitude higher than that of 3D rGO framework-embedded PDMS composite containing comparable loading of rGO. When subjected to repetitive mechanical stress, it was found that the superior conductivity performance of CGr framework over rGO framework was well retained, presumably due to the higher perfectness of graphitic layers, which would impart much longer electron transfer to the framework architecture of graphitic carbon nanosheets.
Keywords: INTERCONNECTED GRAPHENE NETWORKS; THIN-FILM; FOAM; COMPOSITES; NANOCOMPOSITES; NANOTUBES